Genetically Modified Rice: Do Chinese Consumers Support or Go Against It? Based on the Perspectives of Perceived Risk and Trust - Huo, Lingyu; Liu, Yan (Frontiers in Psychology, 2022)
Rice is a staple food in China, and thus its security has drawn much attention. The Chinese government proactively fuels the application of biotechnology in agriculture and food to cope with increasingly severe food security issues. However, most consumers resist the commercialization of genetically modified (GM) rice. The most probable reason is the consumer perception of its various risks. Conversely, trust in the government, scientists, and media can stimulate consumer purchase. On the basis of the dual perspectives of perceived risks and trust, this study establishes a model of purchase intention for GM rice to explore the structural relationship between variables. Perceived risks explore how exclusion can weaken the purchase intention from the consumer perspective; trust examines the benefits that support can provide. Based on the structural equation model, online survey results of 564 consumers in eight provinces and cities are anlyzed. The following conclusions are drawn: health risks, moral risks, and purchase intention are negatively correlated; environmental, functional, and economic risks have no significant correlation with purchase intention; and trust and purchase intention have a significant positive correlation.